2021
DOI: 10.1111/phn.13023
|View full text |Cite
|
Sign up to set email alerts
|

Children born of genocidal rape: What do we know about their experiences and needs?

Abstract: Background An often under addressed and tragic legacy of genocide is the conception of children from rape. While the experience has been documented from their mothers' perspective, the perspectives and needs of individuals born of genocidal rape has been under‐studied. Methods We conducted an integrative review of all peer‐reviewed articles that reported on studies conducted among individuals born of genocidal rape published through 2020. We used an inductive process to identify and describe the themes from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…These findings therefore suggest that the prenatal stress endured by these individuals is severe and unrelenting and thus not reducible to the 89‐day duration of the genocide itself. Indeed, the consequences of being conceived by genocidal rape persist into childhood and adulthood (Erjavec & Volčič, 2010a; Erjavec & Volčič, 2010b; Uwizeye et al, 2022). Our previous findings indicated that these young adults had significantly worse health outcomes than those who were not conceived via genocidal rape (Uwizeye et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings therefore suggest that the prenatal stress endured by these individuals is severe and unrelenting and thus not reducible to the 89‐day duration of the genocide itself. Indeed, the consequences of being conceived by genocidal rape persist into childhood and adulthood (Erjavec & Volčič, 2010a; Erjavec & Volčič, 2010b; Uwizeye et al, 2022). Our previous findings indicated that these young adults had significantly worse health outcomes than those who were not conceived via genocidal rape (Uwizeye et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Rape in the context of genocide is used as a tool to disappear a racial or ethnic group, and specifically in Rwanda, Hutu extremists used genocidal rape to humiliate the Tutsi and induce a painful death for the victims (Mukamana & Brysiewicz, 2008; Nowrojee, 1996). Both the primary rape victim and her child conceived by that rape experienced lasting trauma, isolation, and discrimination, beyond the pregnancy itself (Uwizeye et al, 2022). In our 2021 study, those adults conceived by genocidal rape had higher adverse childhood experiences scores (ACEs), reflective of the stigma and trauma reported by adult children conceived via genocidal rape to continue into adulthood (Erjavec & Volčič, 2010a; Uwizeye et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the children and adolescents who survived the 1994 genocide—now raising the next generation—are victims of rape, torture, starvation, mutilation, and emotional abuse, have lost at least one of their family members, and/or have witnessed violence, injury, or killing. The physical and emotional trauma parents suffer lead to negative indirect impacts on the lives of Rwandese youth (see Uwizeye et al, 2022 ) and, as well, studies demonstrate the intergenerational transmission of this trauma (see Kahn & Denov, 2022 ).…”
Section: Introductionmentioning
confidence: 99%